Hubungan Antara Kinerja Bidan Dengan Kepuasan Pasien Bersalin Di Wilayah Puskesmas Boyolangu Kabupaten Tulungagung - Tikasari, Selvia, Purwanti, SKM., M.Kes, Anisa Catur Wijayanti, S.KM.,M.Epid (2016)
Unfavourable midwife performance in giving birth help can cause fatal. This matter can affect fatal to mother and its baby, mother death, baby death, handicap at the baby, handicap at the mother, blood birthing pasca (HPP), shoulder distorsia (shoulder cannot go out because mother of running out of energy), packing distres, hypothermia, asphyxia, result of from perception of midwife researcher sometime delay to refer the patient to hospital, where one time giving birth at phase laten too long. Purpose of this research is to know the the correlation of midwife performance with give birth patient satisfaction in society health center of Boyolangu Tulungagung Regency. This research type was observational analysis with cross sectional approach by sampel counted 27 person who was taken with accidental sampling technique. The data analyse technique use chi square test. Result of analysis known the majority of midwife age > 35 years old (62,5%), have an education Midwifery D3 (93,8%), have old work > 5 years (87,5%) and majority midwife have followed APN training (87,5%). While for patients known that majority age between 20-35 years old (74,1%), have an midlle education (Junior High School) (70,4%) and working as housewife (48,1%). From 16 midwife doing giving birth help counted 27 giving birth, at most midwife have the good performance (55,6%) and patient satisfaction from 27 respondents of majority tell to satisfy (51,9%). Research result shows that there was correlation between midwife performance with give birth patient satisfaction in Society Health Center of Boyolangu Tulungagung Regency with p-value 0,013 < 0,05 (POR = 8,25; 95% CI: 1,45 - 46,85).